Understanding the Tourism Area Life Cycle and Sustainability Perceptions in the Rural Destination of Kintamani, Bali - Saputra, I Gede Gian; Pradnyadari, I Gusti Agung; Pidada, Ida Bagus Udayana (Faculty of Economics and Business, University of Mataram, 2025)
This study examines the dynamics of tourism development and sustainability perceptions in Kintamani, Bali, using the Tourism Area Life Cycle (TALC) model. Kintamani, a rural highland destination, has experienced rapid growth in tourism activities, from mass visitation to niche experiences such as glamping and coffee tourism. Despite its popularity, limited research addresses its current life cycle stage and visitors’ sustainability views. A mixed-method approach was applied, combining surveys of 100 domestic and international tourists with in-depth interviews involving six key stakeholders, including local business owners, community leaders, and government representatives. Findings reveal that Kintamani is transitioning from the development to consolidation stage, marked by increasing infrastructural pressures and socio-environmental challenges. While visitors value the area’s natural and cultural assets, they express concerns over waste management and overcrowding. The integration of TALC and sustainability perceptions offers a framework for adaptive destination in rural Bali.